2019
DOI: 10.1002/gch2.201800114
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Uniformity in Ferroelectric KxNa1−xNbO3 Thin Films

Abstract: Potassium sodium niobate (KNN) has long been considered a viable candidate for replacing lead‐based materials in piezo‐ and ferroelectric devices. The introduction of KNN on an industrial scale is highly awaited; however, processing challenges still remain to be solved. The main obstacle is lack of reproducible growth of uniform boules or thin films at temperatures that facilitate monolithic device integration. Herein, atomic layer deposition (ALD) of KNN thin films, exhibiting high chemical uniformity over la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…This could be possible through super cycles of processes for the alkali oxides/oxynitrides/ nitrides/phosphates. Sønsteby et al 46,47 have demonstrated a mixed KNbO 3 -NaNbO 3 using KO t Bu and NaO t Bu as precursors. It was found that the K : Na ratio was tunable to 1% by substituting in NaO t Bu for KO t Bu in the KNbO 3 process.…”
Section: Dalton Transactions Papermentioning
confidence: 99%
“…This could be possible through super cycles of processes for the alkali oxides/oxynitrides/ nitrides/phosphates. Sønsteby et al 46,47 have demonstrated a mixed KNbO 3 -NaNbO 3 using KO t Bu and NaO t Bu as precursors. It was found that the K : Na ratio was tunable to 1% by substituting in NaO t Bu for KO t Bu in the KNbO 3 process.…”
Section: Dalton Transactions Papermentioning
confidence: 99%
“…The material possesses distinct properties in the form of films as compared to their bulk form owing to the altered lattice strain, structural defects, surface area, etc. [26][27][28] Several advanced synthesis techniques, such as RF magnetron sputtering, [29] pulsed laser deposition, [11] chemical vapor deposition, [30] atomic layer deposition, [31] etc., have been used to fabricate the KNN thin films. However, RF magnetron sputtering has been widely used over other deposition techniques because of its high-quality films, uniformity, dense, and large-area deposition.…”
Section: Introductionmentioning
confidence: 99%
“…16 ALD processes for Na-and K-containing compounds were reported in 2014, and have since been expanded to include KNN and KTN, among others. [17][18][19][20][21] The large majority of these processes utilize alkali metal tert-butoxides (e.g. NaO t Bu or KO t Bu, (Fig.…”
Section: Introductionmentioning
confidence: 99%